Influence of biological maturation status on selected anthropometric and physical fitness variables in adolescent male volleyball players - Mario Albaladejo-Saura; Raquel Vaquero-Cristóbal; Juan A. García-Roca; Francisco Esparza-Ros (PeerJ, 2022)
Background The identification of sport talent among adolescent athletes is a topic that in recent years has been a major focus of interest for both the scientific community and sport managers. Both anthropometry and physical performance through fitness tests have demonstrated to be key elements. Biological maturation, due to its influence on anthropometric variables and physical fitness, has also been studied in relation to sport talent identification. Objective To analyse differences according to biological maturation status in anthropometric characteristics and performance in physical fitness tests, and to determine which variables predict better performance in physical fitness tests in adolescent volleyball players. Methods A cross-sectional design was followed to collect the data. A total of 48 male sub-elite volleyball players (14.17 ± 0.73 years) completed a socio-demographic and sports ad hoc questionnaire. Anthropometric variables were measured following the guidelines of the International Society for the Advancement in Kinanthropometry (ISAK) including four basic measurements (body mass, height, sitting height and arm span); eight skinfolds (triceps, biceps, subscapular, iliac crest, supraspinale, abdominal, thigh and calf); four girths (arm relaxed, flexed and tensed arm, middle thigh and calf); five breadths (biacromial, biileocrestal, humerus, femur and bi-styloid); three lengths (acromiale-radiale, radiale-stylion and stylion-medio dactilion); and a height (ilioespinale). Physical fitness was assessed, including the sit-and-reach, back scratch, long jump, medicine ball throw, counter movement jump (CMJ), 20 meters sprint, and agility tests. Furthermore, maturity offset and age at peak height velocity (APHV) was calculated. Results Significant differences were found in the body mass (Mean Difference, MD = 20.86–30.75), height (MD = 11.72–19.09), sitting height (MD = 4.27–10.27), arm span (MD = 12.91–20.78), body mass index (MD = 3.72–5.63), upper limb length (MD = 7.76), corrected muscle girths (MD = 2.06–9.31), ∑6 and 8 skinfolds (MD = 3.67–50.21) fat mass and percentage (MD = 0.30–11.58), muscle (MD = 4.13–10.64) and bone mass (MD = 1.61–3.54) (p < 0.001–0.030), showing higher values the early maturers. In the physical fitness tests, significant differences were observed in the medicine ball throw (MD = 1.26–2.80) and in CMJ power (MD = 156.71–379.85) (p < 0.001). Regression models identified fat mass percentage predicted worse physical test performance (p < 0.001), while age, maturation offset, muscle and bone variables were predictors of better physical performance (p < 0.001). Conclusions Significant differences based upon the stages of biological maturation were found in the anthropometric and physical condition variables in favor of the players whose maturation process was more advanced, with the variables related to fat and adipose, muscle and bone development conditioning their performance in the physical condition tests.